Using drone brood in the control of the Varroa disease of bees in Greece - Santas, L.A.; Lazarakis, D.M. (ENTOMOLOGIA HELLENICA, 1984)
The use of drone brood to control the Varroa disease (Varroa jacobsoni Ouds) was tested in twenty bee colonies (ten as control) which had a very low Varroa mite infestation. The experiment started in winter 1981-82. Early in spring 1983 the brood was removed from ten hives and later during April, May and June it was replaced by drone combs (trap combs) which were also removed when drone cells were capped. The same treatment was repeated during spring 1984. In July 31, 1984, the adult bee infestation was 0 to 7%, while the worker brood’s infestation was 0 to 17%. The data show that, after two and half years without any acaricidal treatment, six out of the ten bee colonies continued to have a very low mite infestation, while three showed high infestation and had to be treated with acaricide. One of the three colonies was treated by acaricide in the winter 1983-84, that is two years from the beginning of this experiment. On the contrary, in the ten control colonies (with the same low infestation in spring 1982) the mite infestation reached catastrophic levels by August 1983.